EDUKASI PENGELOLAAN LIMBAH BERKELANJUTAN BAGI PENGELOLA MAKAM: STUDI KASUS DI ZIARAH MAKAM GURU ZUHDI BANJARMASIN - Amima, Sharfina Puteri; Rahmattullah, Muhammad; Bahar, Syaripudin (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2025)
Banjarmasin, a city rich in culture and pilgrimage traditions, faces a significant environmental problem with the accumulation of organic waste from pilgrimage flowers, especially in the Guru Zuhdi's Tomb area. Based on observations, the volume of flower waste at the main pilgrimage site can reach 3-5 kg per day and drastically increase to 10-20 kg per day during the haul season. This condition exacerbates the city's organic waste burden, which in 2023 accounted for 55.89% of Banjarmasin's total daily waste generation, equivalent to 170,275.42 tons. Therefore, a community service program was designed to address this issue through comprehensive education. This study aims to educate cemetery managers and the surrounding community on the principles of sustainable waste management. The program adopts a holistic approach that includes socialization, training, and mentoring. The initial phase focuses on raising awareness about the negative impacts of unmanaged flower waste, followed by practical training on waste sorting techniques at the source. Furthermore, participants are given demonstrations on simple methods for processing flower waste, such as composting. The program emphasizes the importance of collaboration and active participation from all parties, involving students from the Economics Education Department at Lambung Mangkurat University and the local community. The expected outcome of this program is the formation of an independent working group capable of effectively managing waste in the cemetery area. With increased knowledge and skills, the cemetery managers are expected to apply best practices in waste management, which in turn will significantly reduce the volume of waste sent to landfills. Moreover, the program also aims to foster broader environmental awareness among the community, changing the paradigm of waste from mere trash to a valuable resource, and demonstrating that simple efforts can have a significant impact on environmental sustainability and community well-being.